PRIMARY IMUNE RESPON OF LAYER POST VACCINATED WITH THE EGG DROPS SYNDOME VACCINE - Kencana, Gusti Ayu Yuniati; Suartha, I Nyoman; Wibawa, I Putu Wira Adi (Buletin Veteriner Udayana, 2017)
This study was conducted to determine the primary immune response post vaccination using EDS inactivated vaccine polyvalent. The sample used was a commercial layer farm in the village of Tiga, regency of Bangli, Bali. A total of 25 layer which were14 weeks old vaccinated using EDS-76 inactivated vaccine containing polyvalent Newcastle disease antigen virus, infectious bronchitis and egg drop syndrome by intramuscularly injection. Examination of EDS antibody titer using serologic test by Hemagglutination Inhibition (HI) test.  Egg drops syndrome antibody titer checked four times, once before vaccination, and every week for three weeks post-vaccination to see the immune responses. The average antibody titer then analyzed using an univariate of variance test followed by a test of Least Significant Difference, Duncan test and regression analysis. The result showed an increase antibody of EDS was significantly every week post vaccination. The average antibody titers of EDS are 2 2,6 HI unit at one weeks post vaccination, about 2 5,04 HI unit at two weeks post vaccination and  2 6,4 HI unit at three weeks post vaccination.